2016
DOI: 10.1039/c5an02302e
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic drug monitoring in dried blood spots using liquid microjunction surface sampling and high resolution mass spectrometry

Abstract: Dried blood spots (DBS) are a versatile and stable tool for direct clinical blood analysis. Ambient high-resolution mass spectrometry is emerging as a method of choice for their quantitative analysis, for instance in therapeutic drug monitoring. Here, we coupled liquid microjunction surface sampling technology, a so-called Flowprobe, with an Orbitrap mass spectrometer and demonstrated the utility of this set-up for direct quantification of multiple drugs in DBS on filter paper. A three-layer set-up that we had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 42 publications
2
23
0
Order By: Relevance
“…Sealing surface‐sampling probe mass spectrometry (SSSP‐MS) and liquid microjunction surface‐sampling probe mass spectrometry (LMJ‐SSP‐MS) are employed as unilateral extraction techniques. LMJ‐SSP‐MS and SSSP‐MS allow for the extraction of soluble materials (e.g., small molecules such as dyes, drugs, natural products (Gaissmaier et al, ), and larger molecules such as peptides and proteins) on surfaces (e.g., thin layer chromatography plates, thin tissue sections, spotted sample arrays, affinity arrays, stainless steel, glass, glassy carbon, hydrophobic paper, etc.) coupled to direct analysis by MS (Van Berkel & Kertesz, ).…”
Section: Microsamplingmentioning
confidence: 99%
See 1 more Smart Citation
“…Sealing surface‐sampling probe mass spectrometry (SSSP‐MS) and liquid microjunction surface‐sampling probe mass spectrometry (LMJ‐SSP‐MS) are employed as unilateral extraction techniques. LMJ‐SSP‐MS and SSSP‐MS allow for the extraction of soluble materials (e.g., small molecules such as dyes, drugs, natural products (Gaissmaier et al, ), and larger molecules such as peptides and proteins) on surfaces (e.g., thin layer chromatography plates, thin tissue sections, spotted sample arrays, affinity arrays, stainless steel, glass, glassy carbon, hydrophobic paper, etc.) coupled to direct analysis by MS (Van Berkel & Kertesz, ).…”
Section: Microsamplingmentioning
confidence: 99%
“…LMJ‐SSP‐MS is useful for therapeutic drug monitoring in DBSs, which (i) minimizes additional sample preparation, (ii) allows for very small sample volumes (2 µL), and (iii) has enhanced sensitivity compared to other direct analysis techniques such as DESI‐MS. The enhanced sensitivity is attributed to the direct ESI processes (Gaissmaier et al, ).…”
Section: Microsamplingmentioning
confidence: 99%
“…Gaissmaier et al reported using a commercialized version of LMJ-SSP, Flowprobe (Prosolia), for TDM with DBS samples. 100 The LOQ for acetaminophen was determined to be 5 μg/mL, although the sensitivity of method was limited, it was still appropriate for acetaminophen (10-20 μg/mL), covering the entire therapeutic range. LMJ-SSP was also coupled with online photochemical Paternò-Büchi reaction to perform rapid in situ determination of lipid C=C location isomers in tissue samples (Fig.…”
Section: Direct Profiling Of Clinical Samplesmentioning
confidence: 99%
“…Interestingly, the use of direct MS methods including in situ extractions, for example DESI (desorption electrospray ionization)-and LMJ-SSP (liquid microjunction surface sampling probe)-MS, for dyestuff analyses of ancient textiles was until now not reported, although these methods were successfully applied in biochemical and forensic research. [24][25][26][27][28][29][30][31] In this study, we present the rst rapid and minimally invasive dyestuff analysis under ambient conditions through real-time in situ microextractions of bers by owprobe™-ESI-HRMS (high-resolution MS), a commercial LMJ-SSP device coupled with an Orbitrap mass analyzer. This system uses a pair of coaxial capillaries (probe outer diameter ¼ 630 mm) being positioned close to the surface of the examined object.…”
Section: Introductionmentioning
confidence: 99%